Microevolution during Chronic Infection May Lead T. asahii to Coexist with the Host - Gen Ba; Xuelian Lv; Xin Yang; Wenling Wang; Junhong Ao; Rongya Yang (Dermatology Research and Practice)
Background. Trichosporon asahii (T. asahii) is part of the cutaneous fungal microbiota in humans and can cause lethal opportunistic infection. During infection, microorganisms can adapt to their environment by adjusting gene expression and cellular activities. Objectives. Investigation of the microevolutionary changes in T. asahii during chronic infection. Methods. Two T. asahii strains were isolated from a chronic trichosporonosis patient between a 15-year interval, and the microevolutionary changes were compared by the immune response of dendritic cell (DC), mice survival model, and transcriptome sequencing analysis. Results. Compared with the primary T. asahii strain, the microevolved strain induced much lower expression of TNF-α by mice bone marrow-derived DC and had a much superior survival rate, a total of 2212 significantly differentially expressed genes were identified in the microevolved strain, and functional analysis showed significance in the downregulated transcription and metabolic process, especially the valine, leucine, and isoleucine degradation pathways, which were associated with pathogenicity and virulence; hence, the results were highly consistent with the decreased immunogenicity and virulence of the microevolved strain. Conclusions. These results demonstrated that the microevolution during chronic infection could induce changes in immunogenicity, virulence, and transcriptome, which might lead T. asahii to coexist with the host.